State-dependent fertility in pinnipeds: contrasting capital and income breeders. - Boyd, Ian Lamont (2000)
1. The study tested the hypothesis that the occurrence of pregnancy in mammals that are capital breeders will be most closely related to state variables that are indices of food stores. Income breeders would not be expected to have the same relationship. 2. The study examined the relationships between mass, time of year, age and body length with the occurrence of pregnancy in three species of pinniped. This included two capital breeders (Crabeater Seal, Lobodon carcinophagus Hombron & Jacquinot, and Grey Seal, Halichoerus grypus Fabricius) and one income breeder (Antarctic Fur Seal, Arctocephalus gazella Peters). Multiple logistic regression analysis was used to examine the relationships and the interactions between the different state variables. 3. In both the capital breeders the state variables used in the study explained approximately twice the amount of variability (55% compared with 25%) in the occurrence of pregnancy than in the income breeder. Mass was the dominant state variable among both the capital breeders whereas in the income breeder mass was less important both relative to other state variables and in absolute terms. The results support the conclusion that the occurrence of pregnancy in capital breeders is more sensitive to body reserves than it is in income breeders. 4. The results also support the conclusion that life histories are the end result of a variety of functional responses to different state variables that have differing degrees of influence. In particular a size-structured approach to studies of population dynamics in pinnipeds may be a more informative way of predicting population responses to environmental variability than the more traditional age-structured approach.